The Dynamics of Frame-bridging: Exploring the Nuclear Discourse in Scotland. Issue 2 (May 2017) - Brown, Antje
Abstract : Simple indicative factors such as political populism and resource abundance cannot fully explain the Scottish Government's anti-nuclear energy policy. To grasp the current policy stance, it is necessary to pay attention to the wider contextualisation of policy framing and specifically the dynamic of story-telling and frame-bridging that ultimately feeds into governmental policy. The Scottish Government's decisive 'no' to a new nuclear fleet can be better understood by considering the underlying (and deliberate) bridging of policy frames that is noticeable between environmental, pacifist, and Scottish independence actors. This bridging not only affects the individual sets of story-telling but also develops a dynamic that reinforces individual stories and transcends well beyond the groups' original remit and objectives. With the help of policy framing analysis, research interviews and documentary analysis, the article explores the dynamic connections between anti-nuclear and independence activists and their causes in Scotland. The article highlights their triangular bridges in terms of personnel, language and story-telling and argues that these are instrumental in shaping the Scottish Government's anti-nuclear energy policy.